Stethopedia: an e-learning resource for medical students to supplement Canadian clinical skills education - Mao, Randi Q; Sandhu, Gurinder; Kerzner, Sophia; Sreeraman, Shreyas; Patel, Janhavi Nikhil; Liu, Eva Yiguan; Singh, Chad B; Profetto, Jason (Canadian Medical Education Journal, 2021)
Implication Statement Online clinical skills videos can supplement teaching and allow for greater flexibility when learning physical examination skills. There are currently few open access clinical skills video resources available for Canadian medical students. Stethopedia is an easy-to-use, open-access library of clinical skills teaching videos based on the Canadian medical curriculum. We created Stethopedia to increase accessibility to clinical skills resources and improve the competency and confidence of medical students performing clinical skills on examinations and clerkship rotations. Medical students would benefit from similar resources based on their school’s specific curriculum in order to improve clinical skill performance.